Team Building and Employee Behaviour: The Role of Employees Sports Involvement, Work Environment, and Participated Leadership - Vimala Venugopal Muthuswamy, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The cultivation of healthy Work Environments, coupled with the enhancement of Employee Behaviour through effective team building, holds significant importance. There is an increasing scholarly focus on examining the impact of employees' participation in sports on team dynamics and interpersonal relationships within the workplace. The behaviour of employees is significantly impacted by the Work Environment, encompassing both the physical setting and the organisational culture. Furthermore, the implementation of participatory leadership fosters a sense of unity within the team and enhances overall performance through the engagement of team members in the decision-making process. Hence, the objective of this research is to examine the correlation among engagement in sports, the Work Environment, and participative leadership, thereby illustrating their collective impact on team cohesion and Employee Behaviour within contemporary organisational settings. The study was conducted by the researcher using a deductive approach grounded in quantitative research methodology. Research findings indicate a positive correlation between employees' engagement in sports activities, enhanced teamwork, and overall workplace conduct. Moreover, empirical evidence suggests that the presence of a conducive Work Environment, coupled with the implementation of participative leadership practices, significantly contributes to the development of a positive organisational culture and the promotion of desirable employee conduct. Nevertheless, the research has predominantly utilised quantitative data, thereby excluding qualitative perspectives that could provide a more comprehensive understanding of the underlying concepts driving the observed correlations.